Main trends in the development of copyright in the European Union - Valentyna Trotska (Теорія і практика інтелектуальної власності)
The article examines the current state and key trends in the development of EU copyright protection. Over the past decades, the EU has enhanced copyright protection, surpassing the standards established in international copyright treaties. This progress has been driven by the continuous development of national legislation in EU Member States and the adoption of EU Copyright Directives. The article identifies key factors that have shaped EU copyright legislation, including the rise of information technology and the Internet, efforts to establish an internal market by fostering copyright-based industries, the need to overcome trans-territorial restrictions, and the goal of creating a competitive economy across EU Member States. However, the author also highlights shortcomings in the formation of EU copyright legislation, such as fragmentation, inconsistencies in regulatory models, and the discretionary power of Member States in implementing EU Directives. Further improvements in EU copyright protection require ensuring a fair and effective balance between public and private interests. One pressing issue is the territoriality of copyright legislation, which has become particularly relevant with the expansion of the digital environment. The article explores the potential for introducing a unified copyright law across all EU Member States by systematizing existing legislation and adopting EU Regulations. Despite progress, unresolved issues remain, and the evolving digital landscape continues to present new challenges that require legal responses. In particular, the regulation of legal relations concerning artificial intelligence development demands further attention. Based on an analysis of EU legislation and identified challenges, the author outlines key directions for future legislative development aimed at strengthening the internal market, addressing trans-territorial restrictions, and achieving an effective balance between public and private interests.